Prevalence, Perception, and Practice, and Attitudes Towards Self-Medication Among Undergraduate Medical Students of Najran University, Saudi Arabia: A Cross-Sectional Study - Al-Qahtani AM; Shaikh IA; Shaikh MAK; Mannasaheb BA; Al-Qahtani FS (Dove Medical Press, 2022)
Awad Mohammed Al-Qahtani,1 Ibrahim Ahmed Shaikh,2 Mohammed Ashique K Shaikh,3 Basheerahmed Abdulaziz Mannasaheb,4 Faisal Saeed Al-Qahtani5 1Department of Family and Community Medicine, College of Medicine, Najran University, Najran, Saudi Arabia; 2Department of Pharmacology, College of Pharmacy, Najran University, Najran, Saudi Arabia; 3Pharmacy Services Division, Najran University Hospital, Najran, Saudi Arabia; 4Department of Pharmacy Practice, College of Pharmacy, AlMaarefa University, Riyadh, 13713, Saudi Arabia; 5Department of Family and Community Medicine, College of Medicine, King Khalid University, Abha, Saudi ArabiaCorrespondence: Awad Mohammed Al-Qahtani, Department of Family and Community Medicine, College of Medicine, Najran University, Najran, Saudi Arabia, Tel +966 530540450, Email awadresearch17@gmail.comBackground: Self-medication (SM) is a customary practice around the globe. Appropriate SM comes with many advantages, yet irrational SM is a concern and could lead to adverse drug events and poor health outcomes.Methods: This college-based cross-sectional study was carried out from January to March 2021 among Najran University undergraduate medical students to investigate the prevalence and practice of, and attitudes towards SM. Data were collected using a bilingual self-administered online questionnaire, which was categorized into sections, such as socio-demographic details, attitude towards SM, and practice of SM during the last six months, along with students' opinions and suggestions regarding SM. The three-item scale was used to assess the students' attitude. IBM SPSS was used to perform the cross-tabulation, chi-squared test, and binary logistic regression.Results: Overall, 205 undergraduate medical students (58.6%) responded to the survey. The overall prevalence of SM was 60%, of which 25% used antibiotics as SM drugs. Headache (65.9%), fever (30.2%), cold/flu (31.2%), and gastric acidity (28.3%) were common illnesses for which SM was sought, using analgesics and NSAIDs (52.7%), antipyretics (13.7%), and antacid (12.7%) medications. Among the reasons for SM, the illness being minor and quick relief were frequently reported. To rationalize and improve the practice of SM, about half (48.3%) of the students suggested spreading awareness and education regarding the implications of SM and dispensing the medications with prescriptions (46.8%).Conclusion: Overall, the attitude towards SM was satisfactory. The prevalence of SM during the last six months was 60%, and antibiotics were used by 25% of students. A significant negative correlation was observed between attitudes towards and practice of SM. Although medical students of Najran University displayed responsible behavior towards SM, efforts should be made to educate them about the adverse consequences of SM, especially with antibiotics.Keywords: self-medication, students, practice, prevalence, Saudi Arabia